Incorporation of Nanoparticles into Inorganic Salt Crystals (review) - Vorontsov, D.; Khalavka, Yu.; Okrepka, G. (Physics and Chemistry of Solid State, 2016)
This article provides an overview of the literature data on the incorporation of nanoparticles into crystals of inorganic salts, particularly alkali metal halides, potassium dihydrogen phosphate and others. The description of methods of obtaining composite crystals salt:nanoparticles, their properties and practical application are overviewed. It is shown that the process of incorporation of nanoparticles into the matrix depends on many factors, so systematic study of the effect of various parameters on its course and efficiency remains actual problem.